IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM MEMPERTAHANKAN KEBERLANJUTAN OPERASIONAL PERUSAHAAN - Prasetya Yoga Santoso; Annisa Larasati (Jurnal Pustaka Komunikasi, 2020)
Routine CSR activities in Water Supply and Sanitation, and Mangrove Ecotourism are practical activities in the form of business that has social responsibility.The paradigm of this research is constructivist. The research approach in this study is qualitative. The method used is a case study. Data collection techniques using in-depth interviews. The data validity technique in this research is triangulation. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results obtained are that the implementation of CSR conducted by Saka Energi is not much different from the CSR framework of CSR implementation by Paul Hohnen. The foundation / basic principle of Saka Energi's CSR program is in accordance with the Triple Bottom Line concept. While the Scholarship and Aid program, Smart House, and Saka Mengajar are business practices in the form of philanthropy. Clean Water and Sanitation Provision Program, Mangrove Ecotourism, Saka Mengajar, and Serial Village in the form of Community Empowerment. Saka Energi's sustainability development program is dominated by community development patterns.